Optimal allocation of monthly water withdrawals in reservoir systems - Ali, M.D. Hazrat; Shui, Lee Teang (Springer, 2001)
In this study, a water balance equation was derived and the performance of a project was analyzed. The water balance components were modeled without calibration, and compared with measured data, whenever possible. A reservoir simulation model was develop and the model storage capacities were compared with the observed storage capacities satisfactorily. An optimization model was developed to solve the water resources of a large project in a computationally satisfactory manner. The optimal reservoir storage, optimal irrigation demand, and optimal reservoir release were computed. The optimal mean (1987-1997) model total water requirements for the dry and wet seasons were also computed and the optimal contributions by rainfall, reservoir, uncontrolled river flow, and recycled water were determined. The mean annual optimal water withdrawals from the reservoir systems were found to be 1223 MCM (Million cubic meters). The optimal mean model total water requirements were compared with other authors computed values for the same and a significant water savings was achieved.